2020
DOI: 10.1111/cts.12780
|View full text |Cite
|
Sign up to set email alerts
|

Population and Noncompartmental Pharmacokinetics of Sodium Oxybate Support Weight‐Based Dosing in Children and Adolescents With Narcolepsy With Cataplexy

Abstract: The pharmacokinetics (PKs) of sodium oxybate (SXB) was evaluated in a subset of participants from a study of SXB treatment in children (aged 7–11 years; n = 11) and adolescents (aged 12–17 years; n = 18) with narcolepsy with cataplexy. PK evaluation was conducted over 2 nights during the period when participants received a stable nightly SXB dose. The SXB dose on night 1 was half of night 2 and was administered in two equally divided doses: dose 1 was administered > 2 hours after the evening meal, and dose 2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(62 reference statements)
0
6
0
Order By: Relevance
“… 20 The PK properties of SXB also were determined to be similar in both adults and children with narcolepsy based on 2 additional PK studies. 94 , 95 A population PK model previously developed to support the SXB pediatric regulatory filing was then adapted to include data from LXB 95 ; this model identified that weight was the major contributing factor to oxybate PK for both SXB and LXB, and showed that a similar dose-exposure relationship existed for SXB and LXB in both adult and pediatric participants with narcolepsy.…”
Section: Approval Of Lxb For Pediatric Patients With Narcolepsymentioning
confidence: 99%
“… 20 The PK properties of SXB also were determined to be similar in both adults and children with narcolepsy based on 2 additional PK studies. 94 , 95 A population PK model previously developed to support the SXB pediatric regulatory filing was then adapted to include data from LXB 95 ; this model identified that weight was the major contributing factor to oxybate PK for both SXB and LXB, and showed that a similar dose-exposure relationship existed for SXB and LXB in both adult and pediatric participants with narcolepsy.…”
Section: Approval Of Lxb For Pediatric Patients With Narcolepsymentioning
confidence: 99%
“…4 The safety and efficacy of SXB for the treatment of cataplexy and EDS in adults and children/adolescents with narcolepsy have been established in randomized controlled trials; commonly observed adverse events included nausea and vomiting. [5][6][7][8][9] The therapeutic effects of SXB in narcolepsy are hypothesized to be mediated through effects at gamma-aminobutyric acid B (GABA B ) receptors on noradrenergic, dopaminergic, and thalamocortical neurons. 4 SXB is administered orally as a solution, diluted before ingestion with 60 mL water, with the total nightly dose typically divided into 2 doses, the first at bedtime and the second 2.5-4 hours later.…”
Section: Introductionmentioning
confidence: 99%
“…In pediatric patients, dosing is based on weight, with an effective dose range of 3–9 g/night 4,5 . The pharmacokinetics (PK) of SXB has been characterized in adult and pediatric populations 6 . SXB is rapidly absorbed (average time to reach maximum plasma concentration [T max ], 0.5–1.25 h) and quickly metabolized and eliminated from the body (average half‐life, 0.5–1 h) 4 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations